Comparison of the Wound Healing Effect of Cellulose and Gelatin: An In Vivo Study - Kang, Bum Sik; Na, Young Cheon; Jin, Young Wan (Archives of Plastic Surgery, 2012)
Background Many topical hemostatics are widely applied for bleeding control. They can be classified into two categories according to their mechanism of action on the clotting cascade in a biologically active or passive manner. Passive hemostatics include cellulose and gelatin. We performed an experimental study to compare the effect of passive hemostatics in wound healing by applying them to a rectus abdominis muscle defect of white mice.Methods Surgicel is a sterile absorbable knitted fabric prepared by the controlled oxidation of regenerated cellulose. Spongostan is an absorbable hemostatic gelatin sponge. In 30 mice, a 1×1 cm defect was created on the rectus abdominis muscle and the materials were applied in three ways: control group, cellulose (Surgicel) group, gelatin (Spongostan) group. For the histologic analysis, biopsies were performed at 3 and 28 days.Results After 3 days, the cellulose group showed limited granulation formation with acute inflammatory reactions similar to the control group. At the 28th day, moderate amounts of granulation tissue formation was observed with milder inflammatory reactions than the control group. In the gelatin group, after 3 days, gelatin remnants were observed surrounded by severe inflammatory changes. After 28 days, the same quantity of gelatin remnants could be still observed.Conclusions This study suggests that cellulose is associated with minimal morbidity in wound healing, while the use of gelatin shows severe adverse tissue reactions with delayed wound healing. Consequently, cellulose is better than gelatin when considering wound healing.
Keywords: Cellulose; Gelatin; Hemostatics; Wound healing